Health Issues of Elderly Women in India: A Gender-responsive Critical Review of Physical, Nutritional, Mental and Social Health - Swati Sucharita; Tapaswini Binakar; Subhashree Jagdev (Archives of Current Research International, 2026)
India is ageing rapidly, and the older population is becoming progressively more female. Women aged 60 years and above outnumber men, survive longer at every advanced age, and are far more likely to be widowed, materially dependent and socially isolated. Their health, nonetheless, is usually examined either as an undifferentiated component of geriatric epidemiology or as a residual category within women’s health research that remains organised around the reproductive years. This critical narrative review evaluates the strength, consistency and limitations of evidence concerning the physical, nutritional, mental and social health of elderly women in India, and assesses whether that evidence supports gender-responsive policy. Literature was identified through structured searching of Europe PubMed Central, PubMed, PubMed Central, OpenAlex, Crossref, the Directory of Open Access Journals, Semantic Scholar and Google Scholar, supplemented by citation tracking and searches of authoritative institutional repositories, with a final search date of 30 June 2026. Evidence was appraised for design adequacy, measurement validity, treatment of confounding, generalisability and consistency, and synthesised thematically rather than study by study. Four findings are robust across independent data sources: older Indian women report and demonstrate more chronic morbidity, functional limitation and depressive symptoms than older men; widowhood is the single most consistent structural correlate of their disadvantage; undernutrition and anaemia coexist with rising adiposity in the same population; and financial dependence constrains care-seeking more severely for women than for men. Several widely repeated claims are weaker than commonly presented, including inferences about causal direction, estimates derived from self-reported diagnosis in a population with limited diagnostic access, and the interpretation of gender gaps in cognition that are confounded by educational attainment. Evidence is thinnest for women aged 80 years and above, for institutional and long-term care, and for intervention effectiveness. Research priorities should shift from repeated cross-sectional description towards longitudinal, measurement-validated and intervention-oriented designs capable of informing gender-responsive geriatric care.